In–out propagator in de Sitter space from general boundary quantum field theory - Daniele Colosi (Physics Letters B, 2015)
The general boundary formulation of quantum theory is applied to quantize a real massive scalar field in de Sitter space. The space–time region where the dynamics of the field takes place is bounded by one spacelike hypersurface of constant conformal de Sitter time. The computation of the amplitude in the presence of a linear interaction with a source field with compact support in the region considered provides the expression of the Feynman propagator which coincides with the so-called in–out propagator.